Analisis dan Sosialisasi Budidaya Lele di Desa Karangsewu, Galur, Kulon Progo - Paramita, Brigitta Laksmi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
The plenty of fish farmers (mostly catfish) and information delivery issue in Karangsewu Village, Kulon Progo urged Group 78 KKN 80 UAJY to do this social service program which focused on the development of catfish aquaculture in the form of integrated catfish business analysis and the proper information delivery method. This program aimed to deliver the knowledge about the development of catfish business by means of all potential things in the village and to deliver the knowledge about proper information delivery method. Data collecting, potency and problem identification, solution and development determination, and application of solution and potency were carried out. The potency of the village consisted of many aspects such as fishery, agribusiness, marine agro, and animal husbandry but fishery is the most potential aspect. The recommended development was aquaculture system which was based on the use of oxygen and microorganism to enhance feed absorption called “bioflok”. The business plan of catfish-based products was also recommended to give an added value equipped with SWOT analysis. The proper information delivery method could be done by means of favorable gathering without resulting in any loss for villagers. This program was expected to increase catfish productivity, to provide an alternative for villagers who need something to do, and to embody good communication in the village.